Kajian Fiqih Muamalah Maliyah dalam Islam di Ciaruteun Ilir dan di Kampung Pemulung - Hasbi Ash Shiddieqy; Sirajudin Khaitami; Muhammad Jamaludin (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2022)
The Most of Moslems do not know about Fiqh Muamalah maaliyah especially at Ciareten Ilir and Kampung Pemulung. The most of studies or discussions at the Mosque are about Fiqh Thoharoh. So, We from the Sahid Bogor Islamic Institute decided to make a discussion or study at the Ciareten Ilir Mosque and Pemulung village about Fiqh Muamalah. The aim of this study is for people to know the differences between Halal and Haram in Islam and to build a central study of Fiqh Muamalah. We provide information to people at the Ciareten Ilir Mosque and village scavengers about Fiqh Muamalah. As a result of this study, people from this location are interested and want to make it like an institution of Fiqh Muamalah.